Abortion Related of Infectious Agents in Women in Thi-Qar Province - Ahmed Faleh Hassun,; Bassim Abdlhussein Jarulla, (University of Thi-Qar Journal of Science, 2021)
This study was conducted in Thi-Qar province for the period from October 2019 to February 2020. During this period, 120 women who underwent abortion out of 1452 pregnant women their ages range from 15 to 45 years old, the control group consisted of 40 pregnant women, ranging in age from 18 to 42 years old. The current study showed that the rate of abortion among pregnant women was 8.26% of them 4.96 is a spontaneous abortion and 3.3% is the first abortion. The current study showed, according to age, that the highest incidence of miscarriage were among women under the age of 25, while the lowest incidence were in women who were between 35 to 45 years old. The current study also indicated, according to body mass index, that the highest incidence of abortion were among women who had a fat body structure, while the lowest incidence were among women who had an overweight body. The results also showed that the incidence of abortion for the first time was higher than the incidence of repeated abortion in relation to age, habitation and body mass index. The results also showed that the highest incidence of abortion for both types was in the second month of pregnancy, while the lowest incidence of abortion was in the eighth month for repeated abortion and in the seventh month for abortion for the first time. With regard to the infection of the studied microorganisms, the current study indicated that the percentage of infection with B. abortus bacteria was 6.7%, while infection with the Parvovirus B19 was 5.8%, while the study did not record any infection with the Trichomonas vaginalis parasite.